PERAN HUTAN TANAMAN RAKYAT DALAM MENINGKATKAN PENDAPATAN DI KESATUAN PENGELOLAAN HUTAN UNIT XIV GEDONG WANI - Anniza Faradhana; Susni Herwanti; Hari Kaskoyo (Forestry Study Program University Of Mataram, 2019)
Community Plantation Forests (CPF) have a very important role in increasing the income for people around the forest. This study aims to see the role of community plantations is in increasing the farmer’s income using Agrosilvopastura cropping pattern. Data collection used observation techniques, interviews, and literature studies. The sampling method used proportional simple random with the number of respondents as many as 90 farmers. Data analysis used income analysis. The results showed that the role of HTR was very influential for the income of farmers 66,25%, compared non CPT (33,75%) with an income value of Rp 2,258,050,000/KK/year or Rp 8,755,863/KK/month using the agrosilvopastura cropping pattern, which was a combination of various agricultural crops (64,20%), forestry (1,36%), and farm (0,69%). Training for farmers and forestry extension workers needs to be carried out to support activities to be more effective and extension workers need to take a more intensive approach to farmers so they can provide solutions and alternative solutions to problems in management.